Health Risk Behaviors and Resilience Among Low-Income, Black Primary Care Patients: Qualitative Findings From a Trauma-Informed Primary Care Intervention Study. Issue 3 (July 2020) - Goldstein, Ellen; Benton, Susan Flowers; Barrett, Bruce
Abstract : This study describes an intervention with low-income, Black primary care patients and their experience in changing a health risk behavior. Participant themes, including behavioral coping, personal values, accomplishments and strengths, barriers and strategies, and social support, are understood in relationship to health behavior theories. Two structured interviews were conducted 1 month apart. Content analysis was used to analyze responses from 40 participants. Participants were well equipped with resilience-based coping, self-efficacies, and informal social networks despite economic and social disadvantages. Findings from this study have the potential to improve behavioral health coping and reduce racial inequities in health prevalent for this population.